1994
DOI: 10.1002/ange.19941060212
|View full text |Cite
|
Sign up to set email alerts
|

Chiroporphyrine: ein Zugang zu asymmetrischen Porphyrinkatalysatoren mit stereogenen Zentren auf der Ringebene

Abstract: Aus leicht zugänglichen chiralen Aldehyden und Pyrrol Können in einem Schritt Porphyrine wie 1 erhalten werden, deren MnCl‐Derivate effektive Katalysatoren für die enantioselektive Epoxidierung nichtfunktionalisierter Olefine sind. neue Impulse für das Design chirotroper Porphyrinliganden dürften sich auch aus der Tatsache ergeben, daß bei der Synthese von 1 bevorzugt dessen D2‐symmetrisches Isomer entsteht, aufwendige Atropisomerentrennungen also entfallen. magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The ruf ‐ and sad ‐deformation systems are commonly used as model ones to simulate the role of heme distortion and investigate spectral properties 12. 25, 26 The dom ‐deformation, which is possibly short of a suitable sample with dom ‐feature, however, has rarely been studied 27…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ruf ‐ and sad ‐deformation systems are commonly used as model ones to simulate the role of heme distortion and investigate spectral properties 12. 25, 26 The dom ‐deformation, which is possibly short of a suitable sample with dom ‐feature, however, has rarely been studied 27…”
Section: Methodsmentioning
confidence: 99%
“…The ruf-and sad-deformation systems are commonly used as model ones to simulate the role of heme distortion and investigate spectral properties. [12,25,26] The dom-deformation, which is possibly short of a suitable sample with domfeature, however, has rarely been studied. [27] Nonplanar porphyrins show an observable out-of-plane feature, and the occurrence of the out-of-plane deformations is generally accompanied with the formation of in-plane components in the macrocycle.…”
mentioning
confidence: 99%
“…So, the distortion is responsible for the symmetry decrease of porphyrin and also favors the macrocyclic inversion and may control electron-transfer rates by stabilizing certain conformers over others. A distorted porphyrin can also induce unique chemical reactivity of the macrocycle giving enantiomeric selectivity in catalytic reactions [29,30,34,35].…”
Section: Gc Electrode Modified With Mnttpcl By Electrochemical Deposi...mentioning
confidence: 99%
“…It can be observed that the oxidation of AA takes place in the 24e62 mV potential range in the case of MnTTPClmodified GC electrodes. The decrease in oxidation potential can be attributed to the increased selectivity of porphyrin-ruffled conformer (the most prevailed deformation of Mn porphyrins [34]) toward binding of AA, thus favoring the oxidation process.…”
Section: Gc Electrode Modified With Mnttpcl By Electrochemical Deposi...mentioning
confidence: 99%